Content Eligibility Analysis of Biology Textbook on The Curriculum 2013 of First Grade (Xst) Senior High School: Covered In Aspect Enviromental Literacy - Syahpitri, Juliana; Febriani, Husnarika; Rohani, Rohani (Universitas Labuhanbatu, 2022)
Textbooks are the crucial factors governing learning sustainability and are also easy to find for students and teachers and learners in the learning process. An analysis of the book is an activity that is carried out to identify the completeness and harmonious content of the book's material. The purpose of this study is to analyze the level of environmental literacy in first grade (x-class) of Senior High School, biology textbook based on the environmental literacy aspect: natural history and ecology, knowledge of environmental issues and issues, cognitive socio-political knowledge, cognitive skills, factors that influence and define responsible behaviour toward the environment, and responsible behaviour toward the environment. The study analyzed three different biological textbooks by publishing. The biology textbook analysis for first grade (x-class) of Senior High School were based on the 2 chapters of environmental literacy, which are ecosystem material and environmental change materials. The study is a descriptive study with content analysis. Instruments in this study use assessment instruments with 6 indicators and 30 statements validator already validated. Based on the analysis, results from a percentage of the book I were Grafindo publisher 31.66% (enough eligible category), Intan Parawirapublisher of were 32.2% (enough eligible category), the Erlangga book showed 32.7% (enough eligible category).